Mica-based fireproof and heat-insulating material for power battery module and preparation method thereof
Patent Information
- Application Number
- CN202611421818.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-14
- Publication Date
- 2026-10-16
AI Technical Summary
[0003]云母是一种层状硅酸盐天然矿物,具有不燃、绝缘、耐酸碱腐蚀的优点,且在高温下无有毒烟气释放,是防火隔热的理想材料;但纯云母板脆性大、抗冲击性能差,在受到外力挤压时易开裂分层;现有技术中,通常采用在云母带表面设置气凝胶来增强其耐高温、隔热性能;但传统的有机气凝胶不具备阻燃性,无机气凝胶机械性能较差,限制了应用范围和应用效果
1、本发明中,制备了含有受阻酚羟基的乙烯基封端有机硅,将其作为软段与丙烯酸丁酯、丙烯酸羟乙酯、甲基丙烯酸甲酯进行自由基聚合,得到有机硅胶粘剂;受阻酚羟基可捕获高温氧化产生的过氧自由基,阻断有机硅在高温下的氧化反应,延缓胶粘剂失效;聚硅氧烷链段在交联网络中起增韧作用,降低固化后胶粘剂的内应力,改善胶粘剂的抗开裂性能。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery thermal insulation materials technology, specifically a mica-based fireproof and thermal insulation material for power battery modules and its preparation method. Background Technology
[0002] In harsh environments, such as fires or punctures, the electrochemical reactions within lithium batteries can release a large amount of heat, leading to thermal runaway. The cell's pressure relief valve can then emit high-temperature flames, which rapidly conduct heat to surrounding cells, potentially causing an explosion. Therefore, power battery modules need to use materials with excellent thermal insulation capabilities to prevent losses caused by thermal runaway.
[0003] Mica is a layered silicate natural mineral with advantages such as non-combustibility, insulation, and resistance to acid and alkali corrosion. It also does not release toxic fumes at high temperatures, making it an ideal material for fireproofing and heat insulation. However, pure mica sheets are brittle and have poor impact resistance, making them prone to cracking and delamination when subjected to external pressure. In existing technologies, aerogels are usually applied to the surface of mica strips to enhance their high-temperature resistance and heat insulation properties. However, traditional organic aerogels do not have flame retardancy, and inorganic aerogels have poor mechanical properties, which limits their application range and effectiveness.
[0004] Therefore, the present invention provides a mica-based fireproof and heat-insulating material for power battery modules and its preparation method to solve the above problems. Summary of the Invention
[0005] The purpose of this invention is to provide a mica-based fireproof and heat-insulating material for power battery modules and its preparation method, so as to solve the problems raised in the prior art.
[0006] To achieve the above objectives, the present invention provides the following technical solution: a mica-based fireproof and heat-insulating material for power battery modules, comprising, from the inside out, a phase change material, an aerogel, and a mica strip; An organosilicon adhesive is coated between the mica tape and the aerogel, and between the aerogel and the phase change material.
[0007] Furthermore, the thickness of the phase change material is 2~5mm; The thickness of the aerogel is 1.5~3.0 mm; The thickness of the mica strip is 0.15~0.30mm; The thickness of the silicone adhesive is 0.03~0.10mm.
[0008] A method for preparing a mica-based fireproof and heat-insulating material for power battery modules includes the following processes: An organosilicon adhesive is coated on the surface of a mica tape and bonded to one side of an aerogel. Then, an organosilicon adhesive is coated on the other side of the aerogel and bonded to a phase change material. After curing, a mica-based fireproof and heat-insulating material is obtained.
[0009] Furthermore, the curing process conditions are: temperature 45~55℃, time 40~90min.
[0010] Furthermore, the silicone adhesive is prepared by the following process: Mix the emulsifier and deionized water, stir well, add butyl acrylate, hydroxyethyl acrylate, methyl methacrylate, β-carboxyethyl acrylate and vinyl-terminated silicone, emulsify for 50-70 minutes to form an emulsion; take 1 / 2 mass fraction of the emulsion, add the initiator, heat to react, then add the remaining emulsion over 3.0-3.5 hours, keep the reaction at the temperature, and adjust the pH to 7.0-8.0 with ammonia water to obtain the silicone adhesive.
[0011] Furthermore, the mass ratio of the emulsifier, deionized water, butyl acrylate, hydroxyethyl acrylate, methyl methacrylate, β-carboxyethyl acrylate, vinyl-terminated silicone, and initiator is 1:(25~35):(15~20):(5~10):(8~12):(0.3~0.8):(5~15):(1.0~2.0).
[0012] Furthermore, the process conditions for the heating reaction are: temperature 76~86℃, time 15~25min; The process conditions for the heat preservation reaction are: temperature 76~86℃, time 1.5~2.5h.
[0013] Furthermore, the emulsifier is one or a mixture of two of emulsifiers CO-436 and AC-1810; The initiator is ammonium persulfate; The concentration of the ammonia water is 15-25%.
[0014] Furthermore, the preparation process of the vinyl-terminated organosilicon is as follows: S1: 1,2-Dichlorobenzene, 2,6-di-tert-butyl-p-methylphenol, N-bromosuccinimide, and benzoyl peroxide are mixed and reacted under nitrogen atmosphere. The mixture is then filtered and distilled under reduced pressure to obtain the modified antioxidant. S2: Mix octamethylcyclotetrasiloxane and tetramethylammonium hydroxide, heat to 60~70℃, add N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane and divinyltetramethyldisiloxane, and react under nitrogen atmosphere to obtain polysiloxane. S3: Mix the modified antioxidant, polysiloxane, tetrahydrofuran and triethylamine, heat to react, and distill under reduced pressure after the reaction to obtain vinyl-terminated organosilicon.
[0015] Furthermore, in S1, the mass ratio of 1,2-dichlorobenzene, 2,6-di-tert-butyl-p-methylphenol, N-bromosuccinimide, and benzoyl peroxide is 1:(0.4~0.8):(0.3~0.5):(0.06~0.10).
[0016] Furthermore, in S1, the process conditions for the heating reaction are: temperature 60~70℃, time 6~9h; The process conditions for vacuum distillation are: temperature 40~50℃, time 1.5~2.5h.
[0017] Furthermore, in S2, the mass ratio of octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane and divinyltetramethyldisiloxane is (100~120):(0.05~0.10):(6~10):(4~6).
[0018] Furthermore, in S2, the process conditions for the heating reaction are: temperature 100~115℃, time 4~5h.
[0019] Furthermore, in S3, the mass ratio of modified antioxidant, polysiloxane, tetrahydrofuran and triethylamine is 1:(1.0~1.5):(4~8):(0.25~0.40).
[0020] Furthermore, in S3, the process conditions for the heating reaction are: temperature 45~50℃, time 3.5~4.5h; The process conditions for vacuum distillation are: temperature 40~50℃, time 1.5~2.0h.
[0021] In the above technical solution, firstly, benzoyl peroxide is thermally decomposed to generate free radicals, which initiate the bromination of 2,6-di-tert-butyl-p-methylphenol by N-bromosuccinimide to obtain a modified antioxidant; then, octamethylcyclotetrasiloxane is ring-opened by tetramethylammonium hydroxide catalysis, and then hydrolyzed and condensed with N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane to introduce an amino group. Divinyltetramethyldisiloxane is used as a capping agent, retaining the vinyl groups at both ends, to obtain a polysiloxane containing double bonds and an amino group; finally, the amino group of the polysiloxane undergoes nucleophilic substitution with the benzyl bromide of the modified antioxidant to obtain a vinyl-capped organosilicon.
[0022] Furthermore, the phase change material is prepared by the following process: Step A: Mix glutaraldehyde, ethanol, p-vinylbenzylamine, glacial acetic acid and p-methoxyphenol, heat and stir to react, filter, wash and dry to obtain Schiff base intermediate; Step B: Under a nitrogen atmosphere, Schiff base intermediate, DOPO, ethanol and triethylamine are mixed, heated and stirred to react, filtered, washed and dried to obtain DOPO derivative; Step C: Mix dodecyl acrylate, azobisisobutyronitrile, 1,6-ethylene glycol diacrylate, and expanded graphite, heat to 40~45℃, add DOPO derivative, and cure in a mold to obtain a phase change material.
[0023] Furthermore, in step A, the mass ratio of glutaraldehyde, ethanol, p-vinylbenzylamine, glacial acetic acid, and p-methoxyphenol is (0.8~1.2):10:(1.2~1.6):(0.05~0.10):(0.05~0.20).
[0024] Furthermore, in step A, the process conditions for heating and stirring the reaction are: temperature 45~55℃, time 4~6h, and rotation speed 100~150r / min.
[0025] Furthermore, in step B, the mass ratio of Schiff base intermediate, DOPO, ethanol and triethylamine is 1:(1.0~1.2):(7~12):(0.03~0.08).
[0026] Furthermore, in step B, the process conditions for heating and stirring the reaction are: temperature 70~80℃, time 10~12h, and rotation speed 100~150r / min.
[0027] Furthermore, in steps A and B, the drying process conditions are: temperature 60~70℃, time 10~12h.
[0028] Furthermore, in step C, the mass ratio of dodecyl acrylate, azobisisobutyronitrile, 1,6-ethylene glycol diacrylate, expanded graphite, and DOPO derivative is 100:(0.8~1.2):(8~15):(8~18):(10~25).
[0029] Furthermore, in step C, the process conditions for curing in the mold are: temperature 50~60℃, time 1.5~2.5h.
[0030] In the above technical solution, firstly, the aldehyde group of glutaraldehyde is condensed with the amino group of p-vinylbenzylamine to obtain a Schiff base intermediate; then, the Schiff base is added to the PH bond of DOPO, retaining the vinyl group, to obtain a DOPO derivative; finally, using dodecyl acrylate as the base material of the phase change material and 1,6-ethylene glycol diacrylate as a bifunctional crosslinking agent, the double bond of the DOPO derivative is used to polymerize the two materials under the action of azobisisobutyronitrile to obtain the phase change material.
[0031] Furthermore, the preparation process of the aerogel is as follows: Chitosan and deionized water were mixed and dispersed by stirring. Hydrochloric acid and phytic acid aqueous solution were added, and the mixture was heated to react. The mixture was then placed in a mold and refrigerated to obtain a hydrogel. The hydrogel was first placed in anhydrous ethanol and allowed to stand for 20-24 hours, and then placed in cyclohexane and allowed to stand for 20-24 hours. After drying, an aerogel was obtained.
[0032] Furthermore, the ratio of chitosan, deionized water, hydrochloric acid and phytic acid aqueous solution is (0.8~1.2) g : (10~20) mL : (1.0~1.8) mL : (0.3~0.5) g.
[0033] Furthermore, the concentration of the hydrochloric acid is 8~12 mol / L; The phytic acid aqueous solution has a mass fraction of 40-50%.
[0034] Furthermore, the process conditions for the heating and stirring reaction are: temperature 60~70℃, time 1.5~2.5h; The process conditions for refrigerating the mold are: temperature -10~-15℃, time 10~12h; The drying process conditions are: temperature 40~50℃, time 40~48h.
[0035] In the above technical solution, chitosan is used as the substrate and phytic acid is used as the crosslinking agent. Phytic acid dissociates into a large number of phosphate groups in the aqueous phase and crosslinks with chitosan segments through intermolecular hydrogen bonds to form a stable three-dimensional porous structure, thus preparing an aerogel.
[0036] Compared with the prior art, the beneficial effects of the present invention are: 1. In this invention, a vinyl-terminated organosilicon containing hindered phenolic hydroxyl groups was prepared. This organosilicon was then used as a soft segment to undergo free radical polymerization with butyl acrylate, hydroxyethyl acrylate, and methyl methacrylate to obtain an organosilicon adhesive. The hindered phenolic hydroxyl groups can capture peroxide free radicals generated by high-temperature oxidation, blocking the oxidation reaction of organosilicon at high temperatures and delaying adhesive failure. The polysiloxane segments play a toughening role in the crosslinking network, reducing the internal stress of the cured adhesive and improving the crack resistance of the adhesive.
[0037] 2. Phase change materials have a certain latent heat capacity for phase change, but they are prone to combustion when facing extreme environments such as battery thermal runaway. Therefore, flame retardants need to be added to phase change materials to achieve good flame retardant effects. In this invention, the phase change range of docosahexamethicone is 55~66℃, which matches the curing temperature of silicone adhesive. Docosahexamethicone is used as the base material for the phase change material, and DOPO derivatives are added as flame retardants, while expanded graphite is used as a thermally conductive material, resulting in a flame-retardant phase change material with high thermal conductivity. In traditional phase change materials, the flame retardant settles and separates from the phase change material during long-term melting-solidification cycles, leading to a decrease in flame retardant performance. In this invention, DOPO derivatives are grafted into the acrylic acid crosslinking network using a covalent bonding method, resulting in better flame retardant performance. Furthermore, the DOPO derivatives in this invention belong to a phosphorus-nitrogen synergistic flame retardant system, further enhancing the flame retardant performance of the fireproof and heat-insulating material.
[0038] 3. In this invention, the aerogel obtained uses biomass raw materials as the substrate, has a low thermal conductivity, and has good thermal insulation performance. The phase change material, aerogel, and mica tape are combined to form a sandwich structure. The innermost phase change material is close to the battery cell and uses the latent heat of phase change to absorb the heat generated by the battery charging and discharging, thus balancing the battery temperature in the module. The aerogel is set on the outside of the phase change material as a thermal insulation barrier. When the latent heat of the phase change material is saturated, the presence of the aerogel can effectively block the heat transfer from the thermal runaway battery to the surroundings. The outermost mica tape has good flame resistance and can block the flame generated by thermal runaway from spreading to the surroundings. The three-layer structure works together to further improve the flame retardant and thermal insulation performance of the material. Detailed Implementation
[0039] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0040] In the following examples, the relevant raw materials are: emulsifier CO-436; initiator ammonium persulfate; and expanded graphite, model GREAT8461.
[0041] Example 1: A method for preparing a mica-based fireproof and heat-insulating material for power battery modules, comprising the following steps: (1) Preparation of silicone adhesive: S1: 1,2-Dichlorobenzene, 2,6-di-tert-butyl-p-methylphenol, N-bromosuccinimide, and benzoyl peroxide were mixed in a mass ratio of 1:0.8:0.5:0.10 and heated to 70°C for 9 hours under a nitrogen atmosphere. The mixture was then filtered and distilled under reduced pressure at 50°C for 2.5 hours to obtain the modified antioxidant. S2: Octamethylcyclotetrasiloxane and tetramethylammonium hydroxide are mixed and heated to 70°C. N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane and divinyltetramethyldisiloxane are added. Under nitrogen atmosphere protection, the mixture is heated to 115°C and reacted for 5 hours to obtain polysiloxane. In S2, the mass ratio of octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane and divinyltetramethyldisiloxane is 120:0.10:10:6. S3: The modified antioxidant, polysiloxane, tetrahydrofuran and triethylamine were mixed in a mass ratio of 1:1.5:8:0.40 and heated to 50°C for 4.5 h. After the reaction was completed, the mixture was distilled under reduced pressure at 50°C for 2.0 h to obtain vinyl-terminated organosilicon. S4: Mix emulsifier and deionized water, stir evenly, add butyl acrylate, hydroxyethyl acrylate, methyl methacrylate, β-carboxyethyl acrylate and vinyl-terminated silicone, emulsify for 70 min to form an emulsion; take 1 / 2 mass fraction of the emulsion, add initiator, heat to 86℃ and react for 25 min, then add the remaining emulsion within 3.5 h, keep at 86℃ and react for 2.5 h, adjust pH to 8.0 with 25% ammonia water to obtain silicone adhesive; the mass ratio of emulsifier, deionized water, butyl acrylate, hydroxyethyl acrylate, methyl methacrylate, β-carboxyethyl acrylate and vinyl-terminated silicone, and initiator is 1:35:20:10:12:0.8:15:2.0; (2) Preparation of phase change materials: Step A: Glutaraldehyde, ethanol, p-vinylbenzylamine, glacial acetic acid and p-methoxyphenol were mixed in a mass ratio of 1.2:10:1.6:0.10:0.20, heated to 55°C, stirred at 150 r / min for 6 h, filtered, washed, and dried at 70°C for 12 h to obtain the Schiff base intermediate; Step B: Under a nitrogen atmosphere, Schiff base intermediate, DOPO, ethanol and triethylamine were mixed in a mass ratio of 1:1.2:12:0.08, heated to 80°C, stirred at 150 r / min for 12 h, filtered, washed and dried at 70°C for 12 h to obtain the DOPO derivative. Step C: Mix dodecyl acrylate, azobisisobutyronitrile, 1,6-ethylene glycol diacrylate, and expanded graphite, heat to 45°C, add DOPO derivative, pour into a mold, and cure at 60°C for 2.5 hours to obtain a phase change material; the mass ratio of dodecyl acrylate, azobisisobutyronitrile, 1,6-ethylene glycol diacrylate, expanded graphite, and DOPO derivative is 100:1.2:15:18:25. (3) Preparation of aerogel: Chitosan and deionized water were mixed and dispersed by stirring. A 12 mol / L hydrochloric acid solution and a 50% phytic acid aqueous solution were added. The mixture was heated to 70°C and reacted for 2.5 hours. The mixture was then poured into a mold and refrigerated at -15°C for 12 hours to obtain a hydrogel. The hydrogel was first placed in anhydrous ethanol and allowed to stand for 24 hours, then placed in cyclohexane and allowed to stand for 24 hours. After removal, it was dried at 50°C for 48 hours to obtain an aerogel. The ratio of chitosan, deionized water, hydrochloric acid, and phytic acid aqueous solution was 1.2 g: 20 mL: 1.8 mL: 0.5 g. (4) Preparation of mica-based fireproof and heat-insulating materials: A 0.10mm layer of silicone adhesive is coated on the surface of a 0.30mm mica tape and bonded to one side of a 3.0mm aerogel. Then, a 0.10mm layer of silicone adhesive is coated on the other side of the aerogel and bonded to a 5mm layer of phase change material. The mixture is cured at 55℃ for 90 minutes to obtain a mica-based fireproof and heat-insulating material.
[0042] Example 2: A method for preparing a mica-based fireproof and heat-insulating material for power battery modules, comprising the following steps: (1) Preparation of silicone adhesive: S1: 1,2-Dichlorobenzene, 2,6-di-tert-butyl-p-methylphenol, N-bromosuccinimide, and benzoyl peroxide were mixed in a mass ratio of 1:0.6:0.4:0.08 and heated to 65°C for 7.5 h under a nitrogen atmosphere. The mixture was then filtered and distilled under reduced pressure at 45°C for 2.0 h to obtain the modified antioxidant. S2: Octamethylcyclotetrasiloxane and tetramethylammonium hydroxide are mixed and heated to 65°C. N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane and divinyltetramethyldisiloxane are added. Under nitrogen atmosphere, the mixture is heated to 105°C and reacted for 4.5 h to obtain polysiloxane. In S2, the mass ratio of octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane and divinyltetramethyldisiloxane is 110:0.07:8:5. S3: Modified antioxidant, polysiloxane, tetrahydrofuran and triethylamine were mixed in a mass ratio of 1:1.3:6:0.35 and heated to 48°C for 4.0 h. After the reaction was completed, the mixture was distilled under reduced pressure at 45°C for 1.8 h to obtain vinyl-terminated organosilicon. S4: Mix emulsifier and deionized water, stir evenly, add butyl acrylate, hydroxyethyl acrylate, methyl methacrylate, β-carboxyethyl acrylate and vinyl-terminated silicone, emulsify for 60 min to form an emulsion; take 1 / 2 mass fraction of the emulsion, add initiator, heat to 80℃ and react for 20 min, then add the remaining emulsion within 3.3 h, keep at 80℃ and react for 2.0 h, adjust pH to 7.5 with 20% ammonia water to obtain silicone adhesive; the mass ratio of emulsifier, deionized water, butyl acrylate, hydroxyethyl acrylate, methyl methacrylate, β-carboxyethyl acrylate and vinyl-terminated silicone, and initiator is 1:30:18:8:10:0.5:10:1.5; (2) Preparation of phase change materials: Step A: Glutaraldehyde, ethanol, p-vinylbenzylamine, glacial acetic acid and p-methoxyphenol were mixed in a mass ratio of 1.0:10:1.4:0.08:0.15, heated to 50°C, stirred at 130 r / min for 5 h, filtered, washed, and dried at 65°C for 11 h to obtain the Schiff base intermediate. Step B: Under a nitrogen atmosphere, Schiff base intermediate, DOPO, ethanol and triethylamine were mixed in a mass ratio of 1:1.1:10:0.05, heated to 75°C, stirred at 130 r / min for 11 h, filtered, washed and dried at 65°C for 11 h to obtain the DOPO derivative. Step C: Mix dodecyl acrylate, azobisisobutyronitrile, 1,6-ethylene glycol diacrylate, and expanded graphite, heat to 43°C, add DOPO derivative, pour into a mold, and cure at 55°C for 2.0 h to obtain a phase change material; the mass ratio of dodecyl acrylate, azobisisobutyronitrile, 1,6-ethylene glycol diacrylate, expanded graphite, and DOPO derivative is 100:1.0:12:12:20. (3) Preparation of aerogel: Chitosan and deionized water were mixed and dispersed by stirring. A 10 mol / L hydrochloric acid solution and a 45% phytic acid solution were added. The mixture was heated to 65°C and reacted for 2.0 h. The mixture was then poured into a mold and refrigerated at -12°C for 11 h to obtain a hydrogel. The hydrogel was first placed in anhydrous ethanol and allowed to stand for 22 h, then placed in cyclohexane and allowed to stand for 22 h. After removal, it was dried at 45°C for 44 h to obtain an aerogel. The ratio of chitosan, deionized water, hydrochloric acid, and phytic acid solution was 1.0 g: 15 mL: 1.4 mL: 0.4 g. (4) Preparation of mica-based fireproof and heat-insulating materials: A 0.08mm thick silicone adhesive is coated on the surface of a 0.20mm mica tape and bonded to one side of a 2.2mm thick aerogel. Then, a 0.08mm thick silicone adhesive is coated on the other side of the aerogel and bonded to a 3mm thick phase change material. The mixture is cured at 50℃ for 60 minutes to obtain a mica-based fireproof and heat-insulating material.
[0043] Example 3: A method for preparing a mica-based fireproof and heat-insulating material for power battery modules, comprising the following steps: (1) Preparation of silicone adhesive: S1: 1,2-Dichlorobenzene, 2,6-di-tert-butyl-p-methylphenol, N-bromosuccinimide, and benzoyl peroxide were mixed in a mass ratio of 1:0.4:0.3:0.06 and heated to 60°C for 6 hours under a nitrogen atmosphere. The mixture was then filtered and distilled under reduced pressure at 40°C for 1.5 hours to obtain the modified antioxidant. S2: Octamethylcyclotetrasiloxane and tetramethylammonium hydroxide are mixed and heated to 60°C. N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane and divinyltetramethyldisiloxane are added. Under nitrogen atmosphere protection, the mixture is heated to 100°C and reacted for 4 hours to obtain polysiloxane. In S2, the mass ratio of octamethylcyclotetrasiloxane, tetramethylammonium hydroxide, N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane and divinyltetramethyldisiloxane is 100:0.05:6:4. S3: The modified antioxidant, polysiloxane, tetrahydrofuran and triethylamine were mixed in a mass ratio of 1:1.0:4:0.25 and heated to 45°C for 3.5 h. After the reaction was completed, the mixture was distilled under reduced pressure at 40°C for 1.5 h to obtain vinyl-terminated organosilicon. S4: Mix emulsifier and deionized water, stir evenly, add butyl acrylate, hydroxyethyl acrylate, methyl methacrylate, β-carboxyethyl acrylate and vinyl-terminated silicone, emulsify for 50 min to form an emulsion; take 1 / 2 mass fraction of the emulsion, add initiator, heat to 76℃ and react for 15 min, then add the remaining emulsion within 3.0 h, keep at 76℃ and react for 1.5 h, adjust pH to 7.0 with 15% ammonia water to obtain silicone adhesive; the mass ratio of emulsifier, deionized water, butyl acrylate, hydroxyethyl acrylate, methyl methacrylate, β-carboxyethyl acrylate and vinyl-terminated silicone, and initiator is 1:25:15:5:8:0.3:5:1.0; (2) Preparation of phase change materials: Step A: Glutaraldehyde, ethanol, p-vinylbenzylamine, glacial acetic acid and p-methoxyphenol were mixed in a mass ratio of 0.8:10:1.2:0.05:0.05, heated to 45°C, stirred at 100 r / min for 4 h, filtered, washed, and dried at 60°C for 10 h to obtain the Schiff base intermediate. Step B: Under a nitrogen atmosphere, Schiff base intermediate, DOPO, ethanol and triethylamine were mixed in a mass ratio of 1:1.0:7:0.03, heated to 70°C, stirred at 100 r / min for 10 h, filtered and washed, and dried at 60°C for 10 h to obtain the DOPO derivative. Step C: Mix dodecyl acrylate, azobisisobutyronitrile, 1,6-ethylene glycol diacrylate, and expanded graphite, heat to 40°C, add DOPO derivative, pour into a mold, and cure at 50°C for 1.5 hours to obtain a phase change material; the mass ratio of dodecyl acrylate, azobisisobutyronitrile, 1,6-ethylene glycol diacrylate, expanded graphite, and DOPO derivative is 100:0.8:8:8:10. (3) Preparation of aerogel: Chitosan and deionized water were mixed and dispersed by stirring. An 8 mol / L hydrochloric acid solution and a 40% phytic acid solution were added, and the mixture was heated to 60°C and reacted for 1.5 hours. The mixture was then poured into a mold and refrigerated at -10°C for 10 hours to obtain a hydrogel. The hydrogel was first placed in anhydrous ethanol and allowed to stand for 20 hours, then placed in cyclohexane and allowed to stand for 20 hours. After removal, it was dried at 40°C for 40 hours to obtain an aerogel. The ratio of chitosan, deionized water, hydrochloric acid, and phytic acid solution was 0.8 g: 10 mL: 1.0 mL: 0.3 g. (4) Preparation of mica-based fireproof and heat-insulating materials: A 0.03mm silicone adhesive is coated on the surface of a 0.15mm mica tape and bonded to one side of a 1.5mm aerogel. Then, a 0.03mm silicone adhesive is coated on the other side of the aerogel and bonded to a 2mm phase change material. The mixture is cured at 45℃ for 40 minutes to obtain a mica-based fireproof and heat-insulating material.
[0044] Comparative Example 1: Compared with Example 1, the vinyl-terminated silicone was replaced with vinyl polydimethylsiloxane, model HY-1100, and all other conditions remained the same as in Example 1. Specifically: (1) Preparation of silicone adhesive: S4: Mix emulsifier and deionized water, stir evenly, add butyl acrylate, hydroxyethyl acrylate, methyl methacrylate, β-carboxyethyl acrylate and vinyl polydimethylsiloxane, emulsify for 70 min to form an emulsion; take 1 / 2 mass fraction of the emulsion, add initiator, heat to 86℃ and react for 25 min, then add the remaining emulsion within 3.5 h, keep at 86℃ and react for 2.5 h, adjust pH to 8.0 with 25% ammonia water to obtain silicone adhesive; the mass ratio of emulsifier, deionized water, butyl acrylate, hydroxyethyl acrylate, methyl methacrylate, β-carboxyethyl acrylate and vinyl polydimethylsiloxane, and initiator is 1:35:20:10:12:0.8:15:2.0; (2) Preparation of phase change materials: Same as in Example 1; (3) Preparation of aerogel: Same as in Example 1; (4) Preparation of mica-based fireproof and heat-insulating materials: A 0.10mm layer of silicone adhesive is coated on the surface of a 0.30mm mica tape and bonded to one side of a 3.0mm aerogel. Then, a 0.10mm layer of silicone adhesive is coated on the other side of the aerogel and bonded to a 5mm layer of phase change material. The mixture is cured at 55℃ for 90 minutes to obtain a mica-based fireproof and heat-insulating material.
[0045] Comparative Example 2: Compared with Example 1, the DOPO derivative was replaced with DOPO, and all other conditions remained the same as in Example 1. Specifically: (1) Preparation of silicone adhesive: Same as in Example 1; (2) Preparation of phase change materials: The mixture of dodecyl acrylate, azobisisobutyronitrile, 1,6-ethylene glycol diacrylate, and expanded graphite was heated to 45°C, DOPO was added, and the mixture was poured into a mold and cured at 60°C for 2.5 hours to obtain a phase change material. The mass ratio of dodecyl acrylate, azobisisobutyronitrile, 1,6-ethylene glycol diacrylate, expanded graphite, and DOPO was 100:1.2:15:18:25. (3) Preparation of aerogel: Same as in Example 1; (4) Preparation of mica-based fireproof and heat-insulating materials: Same as in Example 1.
[0046] Comparative Example 3: Compared with Example 1, no expanded graphite was added to the phase change material, and all other conditions remained the same as in Example 1, specifically: (1) Preparation of silicone adhesive: Same as in Example 1; (2) Preparation of aerogel: Same as in Example 1; (3) Preparation of mica-based fireproof and heat-insulating materials: A 0.10mm thick silicone adhesive was coated on the surface of a 0.30mm thick mica tape and bonded to one side of a 3.0mm thick aerogel. The mixture was then cured at 55℃ for 90 minutes to obtain a mica-based fireproof and heat-insulating material.
[0047] Comparative Example 4: Compared with Example 1, the vinyl-terminated organosilicon was replaced with vinyl polydimethylsiloxane, model HY-1100, and no expanded graphite was added to the phase change material. All other conditions remained unchanged, the same as in Example 1. Specifically: (1) Preparation of silicone adhesive: S4: Mix emulsifier and deionized water, stir evenly, add butyl acrylate, hydroxyethyl acrylate, methyl methacrylate, β-carboxyethyl acrylate and vinyl polydimethylsiloxane, emulsify for 70 min to form an emulsion; take 1 / 2 mass fraction of the emulsion, add initiator, heat to 86℃ and react for 25 min, then add the remaining emulsion within 3.5 h, keep at 86℃ and react for 2.5 h, adjust pH to 8.0 with 25% ammonia water to obtain silicone adhesive; the mass ratio of emulsifier, deionized water, butyl acrylate, hydroxyethyl acrylate, methyl methacrylate, β-carboxyethyl acrylate and vinyl polydimethylsiloxane, and initiator is 1:35:20:10:12:0.8:15:2.0; (2) Preparation of aerogel: Same as in Example 1; (3) Preparation of mica-based fireproof and heat-insulating materials: A 0.10mm thick silicone adhesive was coated on the surface of a 0.30mm thick mica tape and bonded to one side of a 3.0mm thick aerogel. The mixture was then cured at 55℃ for 90 minutes to obtain a mica-based fireproof and heat-insulating material.
[0048] experiment: Flame retardant performance test: Referring to GB / T2406.2-2009, the oxygen index of mica-based fireproof and heat-insulating materials is tested to characterize their flame retardant performance; Thermal insulation performance test: The thermal conductivity of the mica-based fireproof and heat-insulating material was tested using a thermal conductivity meter to characterize its thermal insulation performance; Phase change latent heat test: The phase change latent heat of the phase change material at 45℃ was tested using a differential scanning calorimeter, with the heating rate controlled at 8℃ / min; Adhesion performance test: Referring to GB / T2792-2014, the peel strength of the silicone adhesive in the mica-based fireproof and heat-insulating material was tested at 23℃ and 45℃ respectively. The experimental data are shown in Table 1 below.
[0049] Table 1 Performance Test Results of Mica-Based Fireproof and Thermal Insulation Materials
[0050] Based on the data in the table above, the following conclusions can be drawn: Compared with Example 1, Comparative Example 1 replaced vinyl-terminated silicone with vinyl polydimethylsiloxane HY-1100. The peel strength at room temperature decreased, and the peel strength at high temperature decreased more significantly. This is because vinyl polydimethylsiloxane HY-1100 does not contain hindered phenolic hydroxyl groups, and cannot block the oxidation reaction of silicone at high temperature. Therefore, silicone adhesives are prone to failure at high temperature. Compared with Example 1, Comparative Example 2, which replaced the DOPO derivative with DOPO, showed a more significant decrease in its oxygen index. This is because DOPO contains only phosphorus, while the DOPO derivative is a phosphorus-nitrogen synergistic flame retardant system, which can further enhance the flame retardant performance of the fireproof and heat-insulating material. Compared with Example 1, Comparative Example 3 did not add expanded graphite to the phase change material, and the latent heat of phase change decreased, indicating that the heat absorption buffering capacity decreased. Compared with Example 1, Comparative Example 4 replaced the vinyl-terminated organosilicon with vinyl polydimethylsiloxane, model HY-1100, and did not add expanded graphite to the phase change material. Except for the flame retardant properties, all other properties decreased significantly. In summary, the preparation of silicone adhesives and phase change materials in this invention can promote the comprehensive improvement of the flame retardant, heat insulation, and high-temperature resistance properties of mica-based fireproof and heat-insulating materials.
[0051] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.
Claims
1. A method for preparing a mica-based fireproof and heat-insulating material for power battery modules, characterized in that: Including the following processes: A silicone adhesive is coated on the surface of a mica tape and bonded to one side of an aerogel. Then, a silicone adhesive is coated on the other side of the aerogel and bonded to a phase change material. After curing, a mica-based fireproof and heat-insulating material is obtained. The phase change material comprises the following components: icosyl acrylate, 1,6-ethylene glycol diacrylate, expanded graphite, and DOPO derivatives.
2. The method for preparing a mica-based fireproof and heat-insulating material for power battery modules according to claim 1, characterized in that: The silicone adhesive is prepared by the following process: Mix the emulsifier and deionized water, stir well, add butyl acrylate, hydroxyethyl acrylate, methyl methacrylate, β-carboxyethyl acrylate and vinyl-terminated silicone, emulsify for 50-70 minutes to form an emulsion; take 1 / 2 mass fraction of the emulsion, add the initiator, heat to react, then add the remaining emulsion over 3.0-3.5 hours, keep the reaction at the temperature, and adjust the pH to 7.0-8.0 with ammonia water to obtain the silicone adhesive.
3. The method for preparing a mica-based fireproof and heat-insulating material for a power battery module according to claim 1, characterized in that: The phase change material is prepared by the following process: Step A: Mix glutaraldehyde, ethanol, p-vinylbenzylamine, glacial acetic acid and p-methoxyphenol, heat and stir to react, filter, wash and dry to obtain Schiff base intermediate; Step B: Under a nitrogen atmosphere, Schiff base intermediate, DOPO, ethanol and triethylamine are mixed, heated and stirred to react, filtered, washed and dried to obtain DOPO derivative; Step C: Mix dodecyl acrylate, azobisisobutyronitrile, 1,6-ethylene glycol diacrylate, and expanded graphite, heat to 40~45℃, add DOPO derivative, and cure in a mold to obtain a phase change material.
4. The method for preparing a mica-based fireproof and heat-insulating material for a power battery module according to claim 2, characterized in that: The preparation process of the vinyl-terminated organosilicon is as follows: S1: 1,2-Dichlorobenzene, 2,6-di-tert-butyl-p-methylphenol, N-bromosuccinimide, and benzoyl peroxide are mixed and reacted under nitrogen atmosphere. The mixture is then filtered and distilled under reduced pressure to obtain the modified antioxidant. S2: Mix octamethylcyclotetrasiloxane and tetramethylammonium hydroxide, heat to 60~70℃, add N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane and divinyltetramethyldisiloxane, and react under nitrogen atmosphere to obtain polysiloxane. S3: Mix the modified antioxidant, polysiloxane, tetrahydrofuran and triethylamine, heat to react, and distill under reduced pressure after the reaction to obtain vinyl-terminated organosilicon.
5. The method for preparing a mica-based fireproof and heat-insulating material for a power battery module according to claim 1, characterized in that: The preparation process of the aerogel is as follows: Chitosan and deionized water were mixed and dispersed by stirring. Hydrochloric acid and phytic acid aqueous solution were added, and the mixture was heated to react. The mixture was then placed in a mold and refrigerated to obtain a hydrogel. The hydrogel was first placed in anhydrous ethanol and allowed to stand for 20-24 hours, and then placed in cyclohexane and allowed to stand for 20-24 hours. After drying, an aerogel was obtained.
6. The method for preparing a mica-based fireproof and heat-insulating material for a power battery module according to claim 2, characterized in that: The mass ratio of the emulsifier, deionized water, butyl acrylate, hydroxyethyl acrylate, methyl methacrylate, β-carboxyethyl acrylate, vinyl-terminated silicone, and initiator is 1:(25~35):(15~20):(5~10):(8~12):(0.3~0.8):(5~15):(1.0~2.0).
7. The method for preparing a mica-based fireproof and heat-insulating material for a power battery module according to claim 3, characterized in that: In step A, the mass ratio of glutaraldehyde, ethanol, p-vinylbenzylamine, glacial acetic acid and p-methoxyphenol is (0.8~1.2):10:(1.2~1.6):(0.05~0.10):(0.05~0.20).
8. The method for preparing a mica-based fireproof and heat-insulating material for a power battery module according to claim 3, characterized in that: In step B, the mass ratio of Schiff base intermediate, DOPO, ethanol and triethylamine is 1:(1.0~1.2):(7~12):(0.03~0.08).
9. A method for preparing a mica-based fireproof and heat-insulating material for a power battery module according to claim 3, characterized in that: In step C, the mass ratio of dodecyl acrylate, azobisisobutyronitrile, 1,6-ethylene glycol diacrylate, expanded graphite, and DOPO derivative is 100:(0.8~1.2):(8~15):(8~18):(10~25).
10. The mica-based fireproof and heat-insulating material prepared by the method for preparing a mica-based fireproof and heat-insulating material for a power battery module according to any one of claims 1-9.